2006
DOI: 10.1080/14034940600590523
|View full text |Cite
|
Sign up to set email alerts
|

COHb% as a marker of cardiovascular risk in never smokers: Results from a population-based cohort study

Abstract: COHb% varied widely between never-smoking men in this urban population. Incidence of CV disease and death in non-smokers was related to COHb%. It is suggested that measurement of COHb% could be part of the risk assessment in non-smoking patients considered at risk of cardiac disease. In random samples from the general population COHb% could be used to assess the size of the population exposed to second-hand smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Thus, a consideration of environmental CO exposure and cardiovascular events as well as cerebral vascular events will be presented initially [28][29][30][31][32][33].…”
Section: Clinical Evidence That Co Is a Procoagulant And Antifibrinolmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, a consideration of environmental CO exposure and cardiovascular events as well as cerebral vascular events will be presented initially [28][29][30][31][32][33].…”
Section: Clinical Evidence That Co Is a Procoagulant And Antifibrinolmentioning
confidence: 99%
“…First, looking at the specific subject's degree of exposure, never smokers in the top quartile of observed circulating COHb (0.91%) were determined to have 3.7-fold the relative risk of cardiovascular events and 2.2-fold the relative risk of death compared to the quartile with the lowest COHb (0.43%) [28]. Increased environmental presence of CO in areas with significant [29] or low [30] air pollution was associated with increased incidence of stroke, and increased workplace exposure to CO [31] in nonsmokers was associated with a 1.97-fold increase in ischemic cardiac death.…”
Section: Clinical Evidence That Co Is a Procoagulant And Antifibrinolmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, relationships have been shown previously between COHb levels and the degree of urbanization (Radford and Drizd, 1982), and between COHb levels in donated blood and urban average ambient CO levels (Lipfert, unpublished memorandum). Further, Hart et al (2006) showed that COHb was associated with all-cause mortality even after controlling for self-reported smoking, and Hedblad et al (2005Hedblad et al ( , 2006 showed that high levels of COHb are associated with cardiovascular risk factors and mortality. However, Bono et al (2007) found that smoking effects dominated COHb findings in urban traffic policemen.…”
Section: Biomarkers and Personal Exposures It Is Widely Recognizedmentioning
confidence: 99%